2021
DOI: 10.1002/ajb2.1774
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics and biogeography of the lungwort lichen in North America support distinct Eastern and Western gene pools

Abstract: Premise: Populations of species with large spatial distributions are shaped by complex forces that differ throughout their ranges. To maintain the genetic diversity of species, genepool-based subsets of widespread species must be considered in conservation assessments. Methods: The population genetics of the lichenized fungus Lobaria pulmonaria and its algal partner, Symbiochloris reticulata, were investigated using microsatellite markers to determine population structure, genetic diversity, and degree of cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In a circum-Antarctic study of Pseudocyphellaria glabra, Widhelm et al [46] found evidence for clades that largely correspond to continental-level regions with few instances of intercontinental gene flow, thus showing some spatial structure, though on a very large spatial scale. In Lobaria pulmonaria, a species with a circumboreal distribution that is rare and patchily distributed in some parts of its range, there is evidence for high levels of isolation by distance in some parts of its range [56] and evidence for gene pools with very large distributions in other parts of its range [57], which is perhaps driven by differing landscapelevel processes occurring among sampled regions. The hypothesized relationship between rarity and migration rates in LFFs remains to be tested in a rigorous framework.…”
Section: Discussionmentioning
confidence: 99%
“…In a circum-Antarctic study of Pseudocyphellaria glabra, Widhelm et al [46] found evidence for clades that largely correspond to continental-level regions with few instances of intercontinental gene flow, thus showing some spatial structure, though on a very large spatial scale. In Lobaria pulmonaria, a species with a circumboreal distribution that is rare and patchily distributed in some parts of its range, there is evidence for high levels of isolation by distance in some parts of its range [56] and evidence for gene pools with very large distributions in other parts of its range [57], which is perhaps driven by differing landscapelevel processes occurring among sampled regions. The hypothesized relationship between rarity and migration rates in LFFs remains to be tested in a rigorous framework.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the processes and factors that have shaped the diversity and distribution of the L. atrobrunnea complex remains enigmatic. How historical processes (Otálora et al 2010; Fernández-Mendoza & Printzen 2013; Widhelm et al 2019), isolation by distance (Walser et al 2005; Widhelm et al 2021), niche differentiation (Guttová et al 2019; Allen et al 2021; Moncada et al 2021) and other factors interacted to give rise to the species diversity in the L. atrobrunnea complex remains to be explored. A robust, comprehensive reconstruction of the evolutionary history of the L. atrobrunnea complex is lacking, and our study highlights the potential of genome-scale datasets for resolving relationships within this complex (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Variation along environmental gradients in the lichen symbiosis Many species of lichenized fungi have broad geographic and climatic ranges, and exhibit significant population structure (e.g. Allen et al 2021, Fernández-Mendoza et al 2011, Muggia et al 2014. Part of the observed population differentiation can be linked to environmental factors, evidenced, e.g., by abrupt, parallel genomic breaks along elevation gradients, separating populations into high and low elevation genetic clusters, which correspond to different climate zones (Dal Grande et al, 2017, Rolshausen et al, 2020, 2022.…”
Section: Variation In Circadian Clock and Temperature-response Compon...mentioning
confidence: 99%